2019
DOI: 10.1039/c9fo01664c
|View full text |Cite
|
Sign up to set email alerts
|

Hydroethanolic plant extracts from Cameroon positively modulate enzymes relevant to carbohydrate/lipid digestion and cardio-metabolic diseases

Abstract: Cameroonian plant extracts inhibit enzymes involved in digestion of sugars and fats, showing potential relevance for cardio-metabolic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 32 publications
5
23
0
Order By: Relevance
“…The phytochemical profiling of extracts deriving from the different species described indicated a wide compositional variability, with specimens (fruits or seeds) from some species showing the presence of a few or single dominating components (e.g., Monodora myristica seeds and Tetrapleura tetraptera fruits) and others containing a complex mix of structurally related and unrelated substances (e.g., fruits from Xylopia parviflora and Aframomum citratum). A few previous studies have reported inconsistent information regarding some of the plant parts from the species investigated in this study, and the details have been discussed elsewhere [12]. However, it is worth noting that the hydroalcoholic extract of Xylopia parviflora, which exhibited the simultaneous presence of potent antioxidant compounds such as caffeic acid derivatives and gallotannins, was the only spice extract found to be mostly active in all the assays employed in this study.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The phytochemical profiling of extracts deriving from the different species described indicated a wide compositional variability, with specimens (fruits or seeds) from some species showing the presence of a few or single dominating components (e.g., Monodora myristica seeds and Tetrapleura tetraptera fruits) and others containing a complex mix of structurally related and unrelated substances (e.g., fruits from Xylopia parviflora and Aframomum citratum). A few previous studies have reported inconsistent information regarding some of the plant parts from the species investigated in this study, and the details have been discussed elsewhere [12]. However, it is worth noting that the hydroalcoholic extract of Xylopia parviflora, which exhibited the simultaneous presence of potent antioxidant compounds such as caffeic acid derivatives and gallotannins, was the only spice extract found to be mostly active in all the assays employed in this study.…”
Section: Discussionmentioning
confidence: 70%
“…In conclusion, in the present study, we found that some Cameroonian spice extracts were able to rescue the ROS-induced intracellular impairment of glucose uptake. The observed potent antioxidant capability of most spice extracts may also be beneficial for several pathological conditions involving increased oxidative stress (chronic inflammation, atherosclerosis, cancer), in addition to improving insulin sensitivity, and may be coupled with our recent work showing their positive modulation of enzymes relevant to carbohydrate/lipid digestion and cardiometabolic diseases [12]. Moreover, the analytical data allowed the identification of some bioactive compounds that could justify the observed biological activities and that should be further characterized using more detailed analytical technologies.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The enzyme inhibition assays were conducted according to the protocol described in the Worthington enzyme manual, with some modifications [ 29 ]. For the alpha-amylase inhibition assay, each food extract was diluted in a range of 0.01 to 40.00 mg/mL.…”
Section: Methodsmentioning
confidence: 99%